Requirements for the Use of Rotary Shafts Used on Roller Looms (Eurasian Scientific Herald, 2022)
To automatically regulate the grain supply, a flap is suspended above the dosing roll on the hinges. It is connected through levers, a roller, a bracket and a roller with a power sensor made in the form of two curtain sensors. The flap forms a feeding gap with the metering roll. The minimum clearance is set manually using a restrictive screw (for striped systems it is approximately 0.35 mm; for grinding